Gamma Knife Neurosurgery in the Management of Intracranial Disorders - Chernov, Mikhail F.; Hayashi, Motohiro; Ganz, Jeremy C.; Takakura, Kintomo; SpringerLink (Online service) (Vienna : Springer Vienna : Imprint: Springer, 2013)
The articles in this volume cover the various options of the optimal management of brain tumors, vascular lesions, and functional disorders. They provide a good balance between microneurosurgery and radiosurgery, presenting also alternative surgical and radiosurgical treatment options with discussions on their advantages and disadvantages. The presentation of multiple treatment methods will help to provide better service to patients. Some papers, specifically highlighting alternative treatment options, are accompanied by editorials prepared by recognized experts in the field. Additional emphasis is put on importance of the advanced neuroimaging techniques for radiosurgical treatment planning and subsequent follow-up.
Practice of Gamma Knife surgery: Concept of robotic Gamma Knife microradiosurgery and results of its clinical application in benign skull base tumors -- Contemporary role of microsurgery, radiosurgery, and stereotactic radiotherapy in management of vestibular schwannomas -- Whether Gamma Knife radiosurgery is really necessary for treatment of patients with vestibular schwannomas?- Do we really still need an open surgery for treatment of patients with vestibular schwannomas?-Stereotactic radiosurgery and hypofractionated stereotactic radiotherapy for management of vestibular schwannomas: Initial experience with 17 cases -- What is the role of radiosurgery in management of sellar tumors?- Role of Gamma Knife radiosurgery in management of pituitary adenomas and craniopharyngiomas -- Role of Gamma Knife radiosurgery in multimodality management of craniopharyngioma -- Role of radiosurgery in management of intracranial malignancies -- Gamma Knife treatment strategy for metastatic brain tumors -- Stereotactic radiosurgery for malignant extracerebral intracranial tumors: Patient selection, efficacy, and technical nuances -- Gamma Knife stereotactic radiosurgery for atypical and malignant meningioma -- Management of non-benign meningiomas with Gamma Knife radiosurgery -- The treatment of cavernoma: An evidence based dilemma? - Microsurgical or radiosurgical management of intracranial cavernomas -- Gamma Knife radiosurgery of brain cavernomas -- Gamma Knife radiosurgery for the treatment of intracranial dural arteriovenous fistulas -- Radiosurgery as a neuromodulation therapy -- Long-term outcome of Gamma Knife surgery using a retrogasserian petrous bone target for classic trigeminal neuralgia -- Complications of Gamma Knife neurosurgery and their appropriate management -- How to control Propofol infusion in pediatric patients undergoing Gamma Knife radiosurgery -- Testing of blood DNA radiosensitivity may be predictive for efficacy of experimental glioma irradiation: Animal study -- Advanced Neuroimaging for Gamma Knife Neurosurgery: Importance of neuroimaging accuracy in radiosurgery -- Optimal visualization of multiple brain metastases for Gamma Knife radiosurgery -- Usefulness of advanced neuroimaging protocol, based on plain and gadolinium-enhanced Constructive Interference in Steady State (CISS) images, for Gamma Knife radiosurgery and planning of the microsurgical procedures for skull base tumors -- Usefulness of Leksell GammaPlan for preoperative planning of brain tumor resection: Delineation of the cranial nerves and fusion of the neuroimaging data, including DTI -- Perspectives of 3T MRI in radiosurgical treatment planning -- Differentiation of the tumor progression and radiation-induced effects after intracranial radiosurgery.
Keywords: Medicine; Neurosurgery; Medicine & Public Health; Neurosurgery